The impact of trade and economic growth on the environment: revisiting the cross-country evidence - Awudu Abdulai; Linda Ramcke (Kiel Institute for the World Economy (IfW), 2009)
This paper explores the interrelations between economic growth, international trade and environmental degradation both theoretically and empirically. Panel data from developed and developing countries for the period of 1980 to 2003 is used and previous critique, especially on the econometric specification, is embedded. In particular, it is not assumed that there is a single link for all countries. Several environmental factors and one sustainability indicator are analyzed for the full sample, regions and income groups. The results indicate that there is an Environmental Kuznets Curve (EKC) for most pollutants, but with several reservations. None of the various hypotheses that concern the link between trade and environmental degradation can be entirely confirmed. If anything, there is modest support for the Pollution Haven Hypothesis (PHH). In addition, there are signs that trade liberalization might be beneficial to sustainable development for rich countries, but harmful to poor ones. However, a sustainable development path is particularly important for developing countries, as the poor are most exposed and vulnerable to the health and productivity losses associated with a degraded environment. Given that developing countries do not usually have the institutional capacities to set up the appropriate environmental policies, it is on developed countries to take the lead in addressing environmental degradation issues and assisting developing countries.
Keywords: F18; Q56; 330; Sustainable development; Pollution Haven Hypothesis; Environmental Kuznets curve; adjusted net saving; Environmental Kuznets Curve; Außenwirtschaft; Wirtschaftswachstum; Umweltbelastung; Nachhaltige Entwicklung; Nord-Süd-Beziehungen; Welt; Entwicklungsländer; Industriestaaten